Strategi Memulai dan Mengembangkan UMKM Yang Berkelanjutan di Desa Kertarahayu - Supratno, Setyo (STMIK Royal, 2025)
This seminar aimed to enhance the understanding of MSME entrepreneurs in business planning, digital marketing, financial recording, and e-commerce utilization.The program began with identifying the needs of MSMEs through observation and discussions, revealing key challenges such as a lack of understanding of long-term business strategies, reliance on traditional marketing methods, and low awareness of systematic financial recording. Additionally, e-commerce platforms had not been optimally utilized. The seminar featured academics, business practitioners, and digital marketing experts who covered topics on sustainable business strategies, digital marketing, financial recording, and e-commerce utilization. The results indicated that participants recognized the importance of digital marketing and personal branding as key strategies to enhance business competitiveness. Understanding of business startup strategies and digital marketing was also relatively strong, while digital financial recording remained a challenge that required further attention. MSMEs in Kertarahayu Village are expected to grow and become more competitive in the digital era.Keywords: business sustainability; digital marketing; e-commerce; financial recording; MSMEs Abstrak: Seminar ini bertujuan meningkatkan pemahaman pelaku UMKM dalam perencanaan usaha, pemasaran digital, pencatatan keuangan, dan pemanfaatan e-commerce. Kegiatan diawali dengan identifikasi kebutuhan UMKM melalui observasi dan diskusi, yang mengungkap kendala seperti kurangnya pemahaman strategi bisnis jangka panjang, ketergantungan pada pemasaran tradisional, serta rendahnya kesadaran akan pencatatan keuangan yang rapi. Selain itu, platform e-commerce belum dimanfaatkan secara optimal. Seminar ini menghadirkan akademisi, praktisi bisnis, dan ahli digital marketing yang membahas strategi bisnis berkelanjutan, digital marketing, pencatatan keuangan digital, dan pemanfaatan e-commerce. Hasil seminar menunjukkan bahwa peserta memahami pentingnya pemasaran digital dan personal branding sebagai strategi utama dalam meningkatkan daya saing usaha. Pemahaman terhadap strategi memulai usaha dan digital marketing juga cukup baik, tetapi pencatatan keuangan digital masih menjadi tantangan yang perlu mendapatkan perhatian lebih lanjut. UMKM di Desa Kertarahayu diharapkan dapat lebih berkembang dan berdaya saing di era digitalKata kunci: keberlanjutan bisnis; pemasaran digital; e-commerce; pencatatan keuangan; UMKM